Sistema radicular de cultivares de painço em resposta à calagem - Silva, Laerte Marques da; Crusciol, Carlos Alexandre Costa [UNESP]; Crusciol, João Henrique [UNESP]; Viegas, Roberto de Almeida (My University, 2010)
The root growth is genetically controlled. There is variability among cultivars and soil factors such as toxicant Al and low contents of Ca and Mg can harm it. The objective of this study was to evaluate the root growth and the shoot growth of millet cultivars in response to liming. The experiment was carried out in pots with 13 dm3 of soil, in greenhouse conditions until 62 days after the emergence of the plants. The used experimental design was completely randomized, in a 2x4 factorial scheme, that is to say,two painço cultivars (AL Mogi e AL Tibagi), and four level of calcareous (0,0; 0,83, 1,67 e 3,34 g dm-3 ), with four replications. Liming promotes increase of the root system and of the aerial parts of the cultivars. The AL Tibagi cultivar presents a root system more tolerant to the low saturation by bases in comparison to the AL Mogi, however, the maximum root growth was occurred in saturations at around 64%. Millet cultivars in high acidity conditions reduce root diameter at the expense of the growth in length.

O crescimento radicular tanto apresenta variabilidade genética entre cultivares, sendo também afetado pelos fatores do solo como Al tóxico e baixos teores de Ca e Mg, que podem prejudicá-lo. O objetivo deste trabalho foi avaliar o crescimento radicular de cultivares de painço em resposta à calagem em solo ácido. O experimento foi conduzido em vasos de 13 dm3 de solo, em condições de casa de vegetação, até 62 dias após a emergência das plantas. O delineamento experimental utilizado foi o inteiramente casualizado, em esquema fatorial 2x4, composto por duas cultivares de painço (AL Mogi e AL Tibagi), e quatro níveis de calcário (0,0; 0,83; 1,67 e 3,34 g dm-3 ) e com quatro repetições. A calagem promove aumento do sistema radicular e da parte aérea das cultivares. A cultivar AL Tibagi apresenta sistema radicular mais tolerante à baixa saturação por bases, e o máximo crescimento radicular ocorreu em saturação por bases de 64%. Condições de elevada acidez do solo reduzem o diâmetro radicular das cultivares de painço à custa do crescimento em comprimento.
Root system of common millet cultivars as response of liming
Keywords: Calcareous; Aluminium; Acid soil; Root; Panicum miliaceum L.; Calcário; Alumínio; Solo ácido; Raiz